Indonesian EFL Teachers' Strategies for Integrating Character Values and Local Culture: A Review of Implementation and Learning Outcomes - Muhammad Agung; Nur Ayu Budiarty; La Sunra (Universitas Islam Negeri Palopo, 2025)
This systematic review synthesizes findings from 23 empirical studies (2023–2025) on how Indonesian EFL teachers integrate local culture and character values into their pedagogy or instructional strategy, following the PRISMA protocol. It addresses a gap in the systematic consolidation of evidence regarding the methods and effectiveness of such integration. The analysis reveals that teachers predominantly utilize local folktales (19 out of 23 studies) as the primary medium for embedding local culture and character values, with research concentrated at the Junior High School level. Vocabulary achievement emerged as the most frequently measured learning outcome, highlighting its role as a foundational skill effectively supported by narrative contexts. The study provides a framework linking the narrative structures of folktales to pedagogical strategies for promoting cultural and character education into EFL classroom. A key practical implication is the need for targeted professional development programs to train teachers in systematically leveraging local folklore. This review’s primary contribution is establishing a foundation for future empirical research to quantitatively assess the efficacy of culturally integrated EFL approaches, thereby bridging national educational mandates with classroom practice.